The crime of failure to provide family assistance: actus reus analysis - Baldino Mayer, Nicolás (2022)
This article is developed after noting that there is a confusion about what would be the legal right protected by the crime of omission of family assistance, that is, if it refers to the family, to the personal integrity of the alimony or the administration of justice. Once the scope of protection has been determined, the concept of "state of necessity" will be analyzed as a food hazard, the limits of applicability of the criminal type on potential circumstances will be defined, we will analyze whether it is a crime of proper or improper omission, as well as the elements that make up the objective type, and finally some objective imputation problems will be considered. The justification of the work lies in granting clear criteria that facilitate argumentation and uniformity in judicial decisions.